12-hour ultra-marathons - Increasing worldwide participation and dominance of Europeans - Sehovic, E.; Knechtle, B.; Rüst, C. A.; Rosemann, T. (Journal of Human Sport & Exercise, 2013)
Ultra-marathon running is of increasing popularity. Participation and performance trends in ultra-marathons have been previously investigated for 100 mile runs, multi-stage ultra-marathons, triathlons and ultra-triathlons, but not for 12-hour runs. We examined participation and performance trends in 12-hour runs held all over the world. Gender, nationality and age in runners competing in 12-hour runs worldwide from 1981 to 2010 were investigated. The annual number of participants in 12-hour runs increased significantly over time for athletes originating from Africa, Asia, Europe, North America and Oceania (P < 0.05). Most of the runners participated in races taking place in the USA and also the most runners originated from the USA, which was followed alternately by Germany and France. Top ten European runners achieved the longest running distances with an average of 134.7±1.9 km for women and 155.8±2.5 km for men, facing the top three nations Russia, Germany and Japan with 130.7±2.6 km and 154.1±3.4 km, 131.8±3.5 km and 146.8±4.1km, 132.1±4.3 km and 144.9±1.3 km for the top ten women and men, respectively. To summarize, participation in 12-hour runs increased in the last 30 years. Europe was the continent with the highest annual number of participants and where the most runners came from. European top ten runners achieved the best performances. Future studies about 12-hour runs need to investigate up to what extent participation and performance trends depend on aspects like age, training, anthropometry, nutrition, experience, and weather.